Using upland rice root traits to identifying N use efficient genotypes for limited soil nutrient conditions - Traoré, K.; Traoré, O.; Bado, V.B. (2013)
Nitrogen (N) deficiency is one of the most yield-limiting nutrients in upland rice growing area in Burkina Faso. A field experiment was carried out from 2008 to 2010 in Farakoba research center with the objective to evaluate 200 upland rice (Oryza sativa L.) genotypes from WAB, NERICA, CNA, CNAX, IRAT and IR lines for N use efficiency. The treatments consisted of three levels of N: low, medium and high at 20, 60 and 100 kg−N ha-1, respectively. Both grain and straw yield increased with N application. The yields were highest for NERICA and WAB lines compared to the other lines, and this was consistent over the N doses. A large variability was found among the genotypes. Three groups of genotypes were identified according to N use efficiency. The high N use efficiency genotypes were found in WAB and NERICA lines. The N concentration in the shoot at flowering significantly increased with N doses and this was similar for N taken up by genotypes